Tendências de consumo digital e seu impacto na promoção de álbuns físicos de K-POP: um estudo de caso sobre o álbum 'Get Up' do grupo Newjeans - Costa, Felipe Gonçalves (Brasil, 2025)
K-pop, a South Korean musical genre, emerged in the late 1990s as part of the "Hallyu" movement, or "Korean wave," which propelled South Korean culture onto the global stage. The popularity of K-pop is due to its combination of diverse musical styles, complex choreography, high-production music videos, and highly trained artists, resulting in a significant influence on global entertainment production. Supported by the South Korean government, K-pop has transformed into an economic force, generating over $4.7 billion annually. This growth is driven by private companies that have invested in the country's culture and media export over the past 20 years. A notable aspect is the impact of K-pop on the revitalization of physical album sales, which, despite the digital boom, remain strong due to innovative marketing strategies and fan engagement. Record labels have adapted their promotion and sales strategies to the digital environment, using online platforms and social media to attract consumers, especially young people, who are the main audience of K-pop. This phenomenon reflects contemporary market dynamics and highlights the economic, social, and cultural impact of K-pop, which transcends geographical and cultural boundaries. This study, by analyzing the album "Get Up" by the group NewJeans, aims to explore how digital consumption trends are shaping the promotion and sales of physical albums in K-pop. The research seeks to provide valuable insights for marketing and promotion strategies in other cultural and creative industries.